Living through sickness in pregnancy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Nursing at Massey University - Wenmoth, Joyce (Massey University, 1997)
This thesis presents a study of the lived experiences of ten women who encountered symptoms of nausea, vomiting and / or retching during their pregnancies. These distressing and debilitating symptoms affect the quality of life of 50-75% of all pregnant women (Rhodes 1990). The thesis provides both a description and a beginning interpretation of the phenomenon of sickness in pregnancy. The four main lifeworld existentials of corporeality (the lived body), relationality (the lived other), spatiality (lived space) and temporality (lived time), as described by van Manen (1990), are used as a guide to reflect on the women's experiences. Disruptive symptoms such as nausea and vomiting seriously affect a woman's experience of the functioning of her body – in particular, it can no longer be taken for granted. The women coped by maintaining control over those aspects of the experience that they could. All women felt that they had been changed by the experience. New meanings had been incorporated in their 'being in the world' not just for the present but for the future. An inability on the part of health professionals to understand the significance of sickness in pregnancy and to comprehend the concerns of these women can result in ineffective care and support. The study offers recommendations for more effective professional care for these women.
Keywords: Morning sickness; Pregnancy complications